New Insights into the Surfactant-Assisted Liquid-Phase Exfoliation of Bi2S3 for Electrocatalytic Applications - Wang, Mengjiao; Crisci, Matteo; Pavan, Matilde; Liu, Zheming; Gallego, Jaime; Gatti, Teresa; Justus Liebig University Giessen (My University, 2023)
During water electrolysis, adding an electrocatalyst for the hydrogen evolution reaction (HER) is necessary to reduce the activation barrier and thus enhance the reaction rate. Metal chalcogenide-based 2D nanomaterials have been studied as an alternative to noble metal electrocatalysts because of their interesting electrocatalytic properties and low costs of production. However, the difficulty in improving the catalytic efficiency and industrializing the synthetic methods have become a problem in the potential application of these species in electrocatalysis. Liquid-phase exfoliation (LPE) is a low-cost and scalable technique for lab- and industrial-scale synthesis of 2D-material colloidal inks. In this work, we present, to the best of our knowledge, for the first time a systematic study on the surfactant-assisted LPE of bulk Bi2S3 crystalline powder to produce nanosheets (NSs). Different dispersing agents and LPE conditions have been tested in order to obtain colloidal lowdimensional Bi2S3 NSs in H2O at optimized concentrations. Eventually, colloidally stable layered nano-sized Bi2S3 suspensions can be produced with yields of up to ~12.5%. The thus obtained low-dimensional Bi2S3 is proven to be more active for HER than the bulk starting material, showing an overpotential of only 235 mV and an optimized Tafel slope of 125 mV/dec. Our results provide a facile top-down method to produce nano-sized Bi2S3 through a green approach and demonstrate that this material can have a good potential as electrocatalyst for HER.
Keywords: bismuth sulfide; low-dimensional material; liquid-phase exfoliation; hydrogen evolution reaction; electrocatalysis; ddc:540